Incidental precancerous and cancerous neoplasms in routine cholecystectomy specimens – A fascinating series of cases in a tertiary care center - Meghadipa Mandal; Debajyoti Singha Roy; Vandana Maroo; Sanghamitra Mukherjee (Asian Journal of Medical Sciences, 2023)
Laparoscopic cholecystectomy is one of the most commonly performed surgeries for benign gall bladder pathologies. Pre-cancerous and malignant gall bladder neoplasms often have overlapping non-specific clinical manifestation in their early stages. Radiological findings are also non-specific in the early stages with the presence of cholelithiasis in a significant proportion of cases. Cholelithiasis is said to be one of the important comorbid risk factors for gall bladder carcinoma (GBC) as a source of constant irritation to biliary mucosa. In such cases, cholecystectomy done for benign indications may lead to a histopathological diagnosis of incidental gall bladder carcinomas. Pancreaticobiliary type of adenocarcinoma is the most common subtype of GBC with two described cases in this series. Invasive foci need to be ruled out in. All cases of high-grade biliary intraepithelial neoplasia as were seen in the third case. Intracholecystic papillary neoplasm is a recently described entity with one reported case in this series that was associated with invasive adenocarcinoma. Signet ring adenocarcinoma is a rarely encountered adenocarcinoma in gall bladder with worse outcome. One such case has been described here where the patient has succumbed to death within 3 months of surgery and during the course of adjuvant therapy.